Characterization of Ti6Al4V powders produced by different methods for selective laser melting - Bo Xie; Yazhuo Fan; Sanchao Zhao (Materials Research Express, 2021)
A comparative investigation was made into Ti6Al4V powders produced by electrode induction melting gas atomization (EIGA), plasma spheroidization (PS), and plasma atomization (PA) in terms of particle size distribution, shape, element distribution, microstructure, flowability and forming properties. The powders were characterized by a laser particle size and shape analyzer, a scanning electron microscopy (SEM), an energy dispersive spectrometer (EDS), an x-ray diffraction (XRD), a Hall-flow meter and SLM machine, respectively. Image analysis was used to quantitatively analyze the elongation and roundness of these Ti6Al4V powders. The results indicate that PA produces the smoothest powder with the lowest satellite sphere. The microstructure of the powders is composed of HCP-α‘ phase. The average elongation and roundness of EIGA Ti6Al4V powder is similar to those of PA Ti6Al4V powder. The flowability of the PA powder (26.23 s/50 g) is better than that of EIGA powder (32.16 s/50 g) and PS powder (35.30 s/50 g). The SLM Ti6Al4V samples produced by EIGA powder exhibit a well-balanced combination of strength (1047 MPa) and ductility (16.2%). In regard to the process of SLM, the PA and EIGA Ti6Al4V powders are more suitable than PS Ti6Al4V powder. The EIGA method is found to be the best choice among these three methods on account of cost and performance.